The detection and treatment of Plasmodium falciparum malaria: time for change. - Nosten, F; Ashley, E (2004)
In most countries where malaria is endemic, P. falciparum malaria is on the rise. This is primarily due to the spread of drug-resistant strains. Drug resistance is mediated by spontaneous changes in the parasite genome that allow resistant parasites to escape the action of the drugs. The spread of drug resistance increases the transmission of malaria parasites. The consequences for the populations at risk are profound both in terms of consequences for health and economy. In order to halt the progression of drug resistance, we need to change the way antimalarials are used. As in tuberculosis and HIV/AIDS, we must use a combination of drugs for the treatment of malaria. Taking into account the pharmacokinetic and pharmacodynamic properties of the various anti-malarial agents, artemisinin-based combination therapy (ACT) seems to be the best option. This strategy should be used in conjunction with early diagnosis and appropriate vector control measures to achieve reduction in the emergence and spread of drug resistance.